Beyond profit: How to create value in business by integrating ESG and sustainability accounting - Musviyanti Musviyanti; Muhammad Abadan Syakura; Muhammad Harits Zidni Khatib Ramadhani (Universitas Hayam Wuruk Perbanas, 2024)
This study aims to explore the integration of Environmental, Social, and Governance (ESG) investment with sustainable accounting practices to achieve the Sustainable Development Goals (SDGs) in order to instill important values in sustainable busi-ness. This study is a qualitative study using a case study method at PT Pupuk Kali-mantan Timur (PKT) and its subsidiary, PT Kaltim Industrial Estate (KIE). Data collection was conducted through in-depth interviews. The findings of this study reveal that a proactive approach to ESG adoption is a strategic corporate initiative that emphasizes corporate governance compliance with government regulations, ethical business practices, and fraud prevention. In addition, this study explores insights into the decision-making process related to ESG projects through budget considera-tions for ESG implementation. The results of this study also indicate that there is an important role for management in adopting ESG practices as a company’s commitment to long-term environmental management. The implications of this study are for sustainable development, especially in the fertilizer industry, through the role of an integrated ESG strategy that will ultimately increase corporate profitability, preserve the environment and support the improvement of community welfare. This research contributes to the practical development of sustainability accounting on how industries can integrate sustainable business with environmental responsibility through ESG initiatives to achieve the SDGs.